Customers Perception on Banking Communication in Development Banks of Kathmandu Valley: Evidence from Structural Equation Modelling (Quest Journal of Management and Social Sciences, 2024)
Background: Effective communication is vital in banking, influencing customer satisfaction and the overall success of banking operations. While global research on banking communication is extensive, studies specific to Nepalese development banks are limited.Objective: The study aims to analyze how customers perceive the communication strategies employed by development banks, identifying challenges and providing recommendations for improvement.Method: An explanatory research design was used, with data collected from 281 customers using KOBO Toolbox and structured questionnaires. The data was analyzed using SPSS, AMOS, and Excel, with Structural Equation Modeling (SEM) applied for inferential analysis.Result: The study found that both formal and informal communication methods are widely used by development banks. However, major challenges include a lack of proper knowledge in digital communication, inadequate communication technology, and ineffective communication strategies. Despite these challenges, good communication was identified as a key factor in customer satisfaction and loyalty.Conclusion: The study concludes that while banking communication is generally effective, there are significant areas for improvement, particularly in digital communication and strategy formulation. Banks are recommended to adopt user-friendly communication technologies, train employees in communication skills, and conduct educational campaigns for customers. By addressing these issues, banks can enhance customer satisfaction and build stronger relationships with their clientele.Paper Types: Research PaperKey words: Banking Communication, Customer's Perception, Loyalty, Trust, Structural Equation Modeling (SEM), Development Bank, Kathmandu Valley.JEL classification: D83, G21, O14, C39, G53